Penerapan Sistem Akuntansi Instansi Berbasis Akrual Sebagai Implementasi PP No. 71 Tahun 2010 pada Politeknik Negeri Pontianak - Zawitri, Sari; Kurniasih, Ninik; Kartikawati, Theresia Siwi (Fakultas Ekonomi dan Bisnis, UNTAN, 2015)
The government regulation (PP) number 71 year 2010 is a new regulation standard of accounting in the public sector. The new regulation standard that inspiring the writers to the research title: Penerapan Sistem Akuntansi Instansi Berbasis Akrual sebagai Implementasi PP nomor 71 tahun 2010 pada Politeknik Negeri Pontianak. The Problems are formulated as (1) The changes of institutional accounting system (SAI) PP 24 year 2005 into PP 71 year 2010 or cash toward accrual into accrual basis? (2) How preparation and the application transition accrual basis institutional accounting system (SAI) or implementation PP 71 year 2010 of the Politeknik Negeri Pontianak? It